Role and Position Political of Martin Luther King 1955- 1957 - Sharif, Hiwa H.; Hamed, Mabast H. (Humanities Journal of University of Zakho, 2019)
This study is a modest attempt to shed light on a prominent American-international figure )Martin Luther King), a prominent political figure in the history of the United States of America and a scientist who gained great fame at a young age due to his political and intellectual activities. )Martin) was very popular in a short period of the second half of the twentieth century, which had a major role in the elimination of violent ideas and change to love, coexistence and peace in the United States of America.The research consists of the introduction, the entrance and the researchers, the entrance of which was devoted to the study of life )Martin Luther King) and stages of study and the origin of his family. The first section contains the beginning of its activity in the state of Alabama. The second topic was devoted to the incident )Rosa Parks) and the role and influence )Martin) in it. In my study, I have relied on different sources of books, especially English.